Parent-Perceived Oral Health of Children With Special Health Care Needs and Developmental Disorders - Elizabeth Alpert; Amy Lin; Kathe Fox; Fan Bi; Jane Barrow; Inyang Isong (JAMA Network Open, 2026)
This cross-sectional study examines the factors associated with parent-perceived oral health status among children with special health care needs and developmental disorders.